Increasing Hemoglobin (Hb) Levels in Pregnant Women with Green Spinach Vegetable Decoction for Pregnant Women - Susilawati; Healthy Junita; Dewi Rostianingsih; Rupdi Lumban Siantar (JOURNAL of HEALTH SCIENCE REVIEW, 2024)
Anemia in general is a condition where the body has too few red blood cells, where the red blood cells contain hemoglobin which functions to carry oxygen to all body tissues (Astrian, 2023:3). Serang Regency with pregnant women has a consumption rate of food containing only iron without Fe 90 as much as 94.7%. This causes anemia in pregnant women to remain high. Objective: analyzed the effectiveness of consuming boiled spinach on increasing hemoglobin levels in pregnant women in the second and third trimesters at the Cinangka Community Health Center. Method: type of quantitative research, the research design is a cross-sectional survey or cross sectional, sampling technique, namely total sampling. Results: parity characteristics of pregnant women: 5 people (41.7%) were primigravida and 7 people (58.3%) were multigravida. After the intervention, hemoglobin levels were carried out, the majority of pregnant women experienced an increase of 12 (100%) to normal hemoglobin levels. The average value of increase in hemoglobin before and after consuming green spinach was 0.67 and results Asymp. Sig. (2 Tailed) of 0.008 that there is a difference in hemoglobin levels before and after being given spinach. Conclusion: respondents in the study before eating green spinach experienced anemia and after the research was carried out there was an increase in pregnant women